Assessment of patellar dislocations in childhood and adolescence Accident-related or predisposition-related? - Schubert,; Dickschas, J.; Strohm, P. C. (Unfallchirurg, 2021)
Background Numerous predisposing factors are known for patellar dislocations but the extent to which these or the trauma cause the dislocation is often unclear. Aim This study investigated whether the analysis of the accident mechanism and anatomical predisposition in juvenile patellar dislocations enables a conclusion as to the causality. Material and methods Retrospective cohort study, evidence level III. In-house employers' liability insurance association (BG) cases with the diagnosis of patella dislocation in patients under 18 years were descriptively evaluated with respect to demographic and predisposing aspects as well as regarding accident information. The accident mechanisms were sorted into subgroups: direct impact, trivial trauma, fall, torsional trauma. Results A total of 54 patellar dislocations were identified with a patient age of 14 years (range 9-18 years). A mild valgus configuration was found in 39% of the cases, on average normal torsion, a tibial tuberosity-trochlea groove (TTTG) distance of 17 mm (range 8-24mm), with 41% a high proportion of patella alta and a trochlear deformity in 57%. Only 20% of the children had no relevant predispositions. The trivial traumas showed the highest proportion of recurrent dislocations with 50% and in the other accident categories the proportion of first dislocations was >75%. In the fall cohort the rate of children without relevant predisposition was highest. Conclusion The predisposition rate in infantile patellar dislocations is high; however, falls are always significant accident events as well as medial direct impact. Torsional trauma is also a significant causative factor, unless high-grade trochlear dysplasia is present, whereas trivial traumas are not.
CRIS-Team WoS Importer:2021-08-27